2004
DOI: 10.2754/avb200473020259
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Repeated Exposure of the Carp (Cyprinus carpio L.) to Cyanobacteria Extract

Abstract: The aim of this study was to examine the influence of a repeated exposure of the carp to the extract of cyanobacteria. We exposed carp embryos and larvae to the extract of cyanobacteria of the cumulative amount of microcystin LR, YR and RR of 1.3 µg⋅l -1 or 13 µg⋅l -1 , respectively. One year later we exposed one half of these fish to the second dose of the extract of cyanobacteria of the cumulative amount of microcystins of 13 µg⋅l -1 and the second half to pure water to eliminate the influence of handling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…A significantly lower count was recorded at higher temperatures in the chlorine treated groups suggesting the inhibitory effect of chlorine affecting the production of erythrocytes, which is generally augmented at higher temperatures. Similar results were reported when Common carp, C. carpio L. were exposed to cyanobacteria extract [39]. An insufficient quantity and quality of red blood cells would therefore consequently have several additional effects on metabolism beyond the function of supplying oxygen for tissue metabolism [32].…”
Section: Discussionsupporting
confidence: 61%
“…A significantly lower count was recorded at higher temperatures in the chlorine treated groups suggesting the inhibitory effect of chlorine affecting the production of erythrocytes, which is generally augmented at higher temperatures. Similar results were reported when Common carp, C. carpio L. were exposed to cyanobacteria extract [39]. An insufficient quantity and quality of red blood cells would therefore consequently have several additional effects on metabolism beyond the function of supplying oxygen for tissue metabolism [32].…”
Section: Discussionsupporting
confidence: 61%
“…Khattab et al (2007) recorded significant decrease in plasma AST and ALT in Oreochromis niloticus fed with diet containing mixture of Micrococcus luteus and Pseudomonas species as probiotic. Also, Palikova et al (2004) and Abd El-Rhman et al (2009) reported the same observation in Cyprinus carpio and O. niloticus fed diet containing extract of Cyanobacteria and Pseudomonas species respectively as probiotics. Mahmoud (2012) mentioned that the highest values of plasma AST and ALT were observed in O. niloticus fed on a diet supplemented with yeast (Saccharomyces cerevisiae), while the lowest value of AST was recorded in fish group fed on a diet supplemented with Bifidobacterium bifiduim.…”
Section: Discussionmentioning
confidence: 52%
“…Lactate dehydrogenase is released from the liver after its cellular damage (Ceron et al, 1997) this may be the reason for the significance decrease in the liver lactate dehydrogenase; thus suggesting that its activity is a sensitive index to measure influence of external factors as supported by the findings of Sastry and Sharma (1980) who reported decreased in lactate dehydrogenase activity in the brain of Channa punctatus exposed to diazinon. Palikova et al (2004) also reported significant decrease in lactate dehydrogenase activity of Carp (Cyprinus carpio L.) with long term exposure to cyanobacteria extract during the early life stages. Rajamanickam and Muthuswamy (2008) reported a decrease in the level of lactate dehydrogenase in the liver homogenate of common carp in a one day exposure to heavy metals with subsequent increase afterwards.…”
Section: Resultsmentioning
confidence: 80%